Long working hours and change in body weight: analysis of individual-participant data from 19 cohort studies - Marianna Virtanen; Markus Jokela; Tea Lallukka; Linda Magnusson Hanson; Jaana Pentti; Solja T. Nyberg; Lars Alfredsson; G. David Batty; Annalisa Casini; Els Clays; Dirk DeBacquer; Jenni Ervasti; et al. (Springer Nature, 2022)
Of the 61,143 participants without overweight/obesity at baseline, 20.2% had overweight/obesity at follow-up. Compared with standard weekly working hours, the age-, sex- and socioeconomic status-adjusted relative risk (RR) of overweight/obesity was 0.95 (95% CI 0.90-1.00) for part-time work, 1.07 (1.02-1.12) for 41-48 weekly working hours, 1.09 (1.03-1.16) for 49-54 h and 1.17 (1.08-1.27) for long working hours (P for trend <0.0001). The findings were similar after multivariable adjustment and in subgroup analyses. Long working hours were associated with an excess risk of shift from normal weight to overweight rather than from overweight to obesity. Long working hours were not associated with weight loss among participants with obesity.\nThis analysis of large individual-participant data suggests a small excess risk of overweight among the healthy-weight people who work long hours.\nTo examine the relation between long working hours and change in body mass index (BMI).\n) among participants with overweight at baseline, and (4) weight loss among participants with obesity at baseline.\nRESULTS\nCONCLUSIONS\nOBJECTIVE\nMETHODS